Interactive SQL Learning Tool with Automated Grading using MySQL Sandbox - Permpool, Tanasab; Nalintippayawong, Srinual; Atchariyachanvanich, Kanokwan (My University, 2019)
This research presents an original tool for automatic grading of SQL statements using MySQL Sandbox[l]. This tool allows students to create and execute the queries in real time. There are many ways to write accurately SQL statement for one question. This is a pain point and burden to the instructors. The existing automated SQL grading algorithms have limitations on supportable statements and understandable error notification. The existing automated SQL grading tool did not support grading on data manipulation language statements i.e. INSERT, UPDATE and DELETE and do not support data definition language commands also; i.e. CREATE, ALTER and DROP. This paper presented an original algorithm which can support these commands. The proposed algorithm can analyze and display the differences between student's answer and correct answer. This algorithm can reduce the instructors' burdens by automatic scoring students' answers and the results directly notify back to both instructors and students. The students can learn and improve themselves faster and effectively.
Keywords: automated grading; data definition language(DDL); data manipulation language(DML); database; grading system; SQL statement